2007
DOI: 10.1007/s11706-007-0065-2
|View full text |Cite
|
Sign up to set email alerts
|

Transformation characteristics of TiNi/TiNi alloys synthesized by explosive welding

Abstract: Effects of severe deformation and heat treatment on the transformation behaviors of explosively welded duplex TiNi/TiNi shape memory alloys (SMAs) were investigated by the differential scanning calorimeter (DSC). The explosively welded duplex TiNi/TiNi plate of 0.7 mm in thickness was cold-rolled at room temperature to the extent of 60% reduction in thickness and then annealed at different temperatures (573-973 K) for different time (15 min-10 h). Low temperature (623-723 K) heat treatment led to amorphous cry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Hence, the TiNi layers, with different Ni concentrations, underwent a B2 ↔ B19' transformation at different temperatures. This is in agreement with the data published in [8][9][10][11][12]. An estimation of the value of heat released and absorbed after cooling and heating as a square under the calorimetric peaks show that the value of the heat effect was smaller than the same value measured in annealed TiNi alloys.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Hence, the TiNi layers, with different Ni concentrations, underwent a B2 ↔ B19' transformation at different temperatures. This is in agreement with the data published in [8][9][10][11][12]. An estimation of the value of heat released and absorbed after cooling and heating as a square under the calorimetric peaks show that the value of the heat effect was smaller than the same value measured in annealed TiNi alloys.…”
Section: Resultssupporting
confidence: 92%
“…To provide the necessary properties, the bimetal composite with an equiatomic TiNi alloy as a shape-memory alloy layer and a Ni-rich TiNi alloy as a pseudo-elastic layer was chosen. First, such composites were produced in [8][9][10][11][12], and Martensitic transformations were studied prior to and following annealing. It was found that the equiatomic TiNi and Ni-rich TiNi layers underwent Martensitic transformations at different temperatures; hence, we might choose a temperature at which the equiatomic TiNi layer was in a Martensite state and the Ni-rich TiNi layer was in an Austenite state.…”
Section: Introductionmentioning
confidence: 99%
“…Explosive welding for joining NiTi to itself was also studied by several authors [50][51][52][53][54][55]. In these studies, two different NiTi alloys, with different compositions and transformation temperatures, were used.…”
Section: Explosive Weldingmentioning
confidence: 99%
“…The objective was to obtain a NiTi/NiTi composite with macroscopic heterogeneities in chemical composition. In [50][51][52]54,55], after explosive welding of NiTi to itself a controlled thickness reduction was performed and the effect of heat treatments on the transformation temperatures to the welded joints was analysed. As expected, by a proper selection of the heat treatment temperature, the martensitic transformation could be adjusted so that the hysteresis of the transformation varied depending on the foreseen application.…”
Section: Explosive Weldingmentioning
confidence: 99%